(3GdNOeGJ GdeUQajI GdGdcJQhfjI s - (3HhYcGR(B, (3YGeQ s; (3hOjY, bGSes ((3GdLRGFQs (3OGQ GdCLjGd GdQbejs, 2023)
(3GdCSS GdfXQjI ddNOeGJ GdeUQajI,GdHfhc GdEdcJQhfjI,CYeGd GdUjQaI GdEdcJQhfjI, cPdc eaghe GdNOeGJ GdeUQajI GdGdcJQhfjI, eQGMd JbOje GdNOeGJ GdeUQajI, hCOhGJgG GdJfXjejI, CfhGY hbfhGJ GdNOeGJ GdeUQajI GdGdcJQhfjI, eGgjI hSGFd GdOaY GdEdcJQhfj aj GdYedjGJ GdeUQajI GdGdcJQhfjI(B.s
Keywords: (3GdHfhc GdEdcJQhfjIs; (3GdOaY GdEdcJQhfjs